Preclinical Complete Dentures Curriculum Survey - Behnoush Rashedi, DMD, MS, MSEd,1 and Vicki C. Petropoulos, DMD, MS2 (Journal of Prosthodontics, 2003)
A survey of U.S. dental schools was conducted in 2001 to determine the curricular structure, teaching philosophies, and techniques used in preclinical complete denture courses.